Designing network on-chip architectures in the nanoscale era - Flich, Jose; Bertozzi, Davide (Chapman & Hall/CRC computational science, 2011)
"Paving the way for the use of network on-chip architectures in 2015 platforms, this book presents the industrial requirements for such long-term platforms as well as the main research findings for technology-aware architecture design. It covers homogeneous design techniques and guidelines, including the solutions that are most appealing to the industry and best suited to meet the requirements of on-chip integration. Each chapter deals with a specific key architecture design, including fault tolerant design, topology selection, dynamic voltage and frequency scaling, synchronization, network on-chip resources exposed to the architecture, routing algorithms, and collective communication"--